KREATIVITAS GURU PENDIDIKAN JASMANI DALAM PEMBELAJARAN PERMAINAN SEPAKBOLA DISEKOLAH MENENGAH PERTAMAA. - Erlina Listyarini (Jurnal Pendidikan Jasmani Indonesia, 2006)
In order to achieve sport lessons objective, the teacher strategy and creativity using toolsand means are required. We use this argument to introduce soccer on junior high schoolstudent. First of all, its not appropriate yet to apply standard rules to them. Because thephysical development on junior high school age are not yet reach the standard level. Thisis why teacher had to modify the game.Boladiator is one of the examples of soccer modification. Using only half of the field eachteam consist of seven players. Another modification is four post soccer, using the availableschoolyard, the student divide equally into four groups. The pembelajaran using modificatedrules required planning, objective, lesson contents, methods, and evaluation.Keyword: Modification, soccer.